PEMAHAMAN KONSEP SISWA SD PADA MATERI KALOR DAN PERPINDAHANNYA DITINJAU DARI GAYA BELAJAR - Sumarli Sumarli; Rien Anitra; Safitri Safitri (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2022)
This study aims to describe the ability of students' conceptual understanding on heat and its transfer in terms of learning styles and the factors that influence them. This research method was descriptive qualitative. The subjects of this study were students of class VA at SD Negeri 83 Singkawang totaling 21 students. Data were collected by using a test technique in the form of a conceptual understanding sheet and a non-test technique in the form of a student learning style questionnaire and interview guidelines. Data analysis techniques used interactive analysis techniques consist of data reduction, data presentation, and drawing conclusions. The results showed that the students' ability of students' conceptual understanding in the visual, auditory, and kinesthetic learning style categories had similarities, namely they less mastering the indicators of exemplifying, classifying, and comparing, and also did not master the indicators of interpreting and explaining; internal factors that affect students' conceptual understanding abilities in the three categories of learning styles, both visual, auditory, and kinesthetic learning styles were weak student memory, low student interest in reading, students are less thorough in understanding questions, and low student writing skills, as well as external factors in the three learning styles, namely the facilities that students get during the online learning process were not maximized and the learning that students do online was less effective.